ANALISIS PEMEROLEHAN BAHASA PADA ANAK USIA DINI DALAM KONTEKS PENDIDIKAN NONFORMAL (STUDI KASUS DI PAUD NONFORMAL AL-QURANIYAH MANNA BENGKULU) - Nelda Sari Siregar; Andre Taulani Sandi; Dina Putri Juni Astuti; Susi Seles; Alfin Julianto; Wiwin Yunita (Comm-Edu (Community Education Journal), 2026)
This study discusses language acquisition in young children aged 5–6 years in non-formal early childhood education.  The issues addressed in this study are language acquisition at the phonological and morphological levels within the context of nonformal education at the Al-Quraniyah Manna Nonformal Early Childhood Education. This study uses descriptive qualitative research. Data collection techniques include observation, listening, recording, note-taking, and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of the study of language acquisition at the phonological level are: First, children aged 5-6 years have acquired the vowel sounds /a/, /i/, /u/, /e/, /ǝ/,/o/. Second, children aged 6 years have acquired the consonant sounds /b/, /c/, /d/, /f/,/g/, /h/, /j/, /k/, /l/, /m/, /n/, /p/, /r/, /s/, /t/, /t/, /y/, and /z/ in conversation, while they can pronounce the consonants /v/, /x/, and /q/, but these consonants have not been found in the conversation of 5-6 year old children,  while 5-year-old children have not yet acquired the consonant sounds /r/, /s/, and /z/ because the consonant /r/ is pronounced as /l/, the consonant /s/ is pronounced as /c/, and the consonant /z/ is pronounced as /j/.  Language acquisition in children at the morphological level involves the process of affixation, which consists of: the prefix (ber-) in the word (berdoa) and (meN-) in the word (menerima), the suffix (-nya) in the word (calanya) and (-lah) in the words (sayangilah), (pegilah) and (ampunilah), as well as confixes (di-, -kan) in the words (ditundukan) and (meN,-i) in the word (menyayangi) as well as the process of repetition (reduplication) of the whole word in (teman-teman) and (meldeka-meldeka).